Estimation of Carbon Footprints from Diesel Generator Emissions - Abdul Qayoom, Jakhrani; Andrew Ragai, Henry Rigit; Othman, A.K.; Saleem, Raza Samo; Shakeel Ahmed, Kamboh (IEEE, 2012)
The aim of this paper is to estimate the amount of carbon footprints emitted from diesel generators in terms of carbon dioxide. A constant load demand of 1.05 kW per hour (6.3 kW/day) with six hours of operation of a diesel generator per day was selected for this analysis. The fuel consumption rate and carbon footprints in terms of carbon dioxide (CO2) were determined. It was discovered that emission of carbon footprints increased by five folds as emission factor was increased from 1kg to 5 kgCO2/liter. Similarly, the increment of a single kW rated power diesel generator at a constant emission factor increases 1.1 to 1.2 times carbon footprint emissions. It is revealed that the efficiency of diesel generator is inversely proportional to its rated power, fuel consumption rate and CO2 emissions. Therefore, the rated power of selected diesel generator should be close to the required load demand.